Cardiac Myosin‐Binding Protein C to Diagnose Acute Myocardial Infarction in the Pre‐Hospital Setting. Issue 15 (6th August 2019) - Kaier, Thomas E.; Stengaard, Carsten; Marjot, Jack; Sørensen, Jacob Thorsted; Alaour, Bashir; Stavropoulou‐Tatla, Stavroula; Terkelsen, Christian Juhl; Williams, Luke; Thygesen, Kristian; Weber, Ekkehard; Marber, Michael; Bøtker, Hans Erik
Abstract : Background: Early triage is essential to improve outcomes in patients with suspected acute myocardial infarction (AMI). This study investigated whether cMyC (cardiac myosin‐binding protein), a novel biomarker of myocardial necrosis, can aid early diagnosis of AMI and risk stratification. Methods and Results: cMyC and high‐sensitivity cardiac troponin T were retrospectively quantified in blood samples obtained by ambulance‐based paramedics in a prospective, diagnostic cohort study. Patients with ongoing or prolonged periods of chest discomfort, acute dyspnoea in the absence of known pulmonary disease, or clinical suspicion of AMI were recruited. Discrimination power was evaluated by calculating the area under the receiver operating characteristics curve; diagnostic performance was assessed at predefined thresholds. Diagnostic nomograms were derived and validated using bootstrap resampling in logistic regression models. Seven hundred seventy‐six patients with median age 68 [58;78] were recruited. AMI was the final adjudicated diagnosis in 22%. Median symptom to sampling time was 70 minutes. cMyC concentration in patients with AMI was significantly higher than with other diagnoses: 98 [43;855] versus 17 [9;42] ng/L. Discrimination power for AMI was better with cMyC than with high‐sensitivity cardiac troponin T (area under the curve, 0.839 versus 0.813; P =0.005). At a previously published rule‐out threshold (10 ng/L), cMyC reaches 100% sensitivity and negative predictive value in patients after 2 hours of symptoms. In logistic regression analysis, cMyC is superior to high‐sensitivity cardiac troponin T and was used to derive diagnostic and prognostic nomograms to evaluate risk of AMI and death. Conclusions: In patients undergoing blood draws very early after symptom onset, cMyC demonstrates improved diagnostic discrimination of AMI and could significantly improve the early triage of patients with suspected AMI.